Predation of a lizard (Plica umbra) by pygmy marmosets (Cebuella pygmaea) in a forest fragment in southwestern Brazilian Amazon - Guilherme, Edson; Canizo, Rodrigo; Araújo, Jailini da Silva (Neotropical Primates, 2016)
No abstract